A Facile Construction of Bisheterocyclic Methane Scaffolds through Palladium‐Catalyzed Domino Cyclization. Issue 10 (24th July 2021) - Qi, Hongbo; Han, Kaiming; Chen, Shufeng
Main observation and conclusion: A convenient palladium‐catalyzed domino cyclization reaction for the construction of bis(benzofuranyl)methane scaffolds bearing an all‐carbon quaternary center has been described. In the cascade process, one C(sp 2 )—O bond, two C(sp 2 )—C(sp 3 ) bonds as well as two benzofuran rings are formed in a single synthetic sequence. The approach shows wide scope of substrates and good functional‐group tolerance. Moreover, this methodology is successfully extended to the synthesis of benzofuranyl methyl chromane derivatives. Abstract : A convenient palladium‐catalyzed domino cyclization reaction for the construction of bis(benzofuranyl)methane scaffolds bearing an all‐carbon quaternary center has been described. In the cascade process, one C(sp 2 )—O bond, two C(sp 2 )—C(sp 3 ) bonds as well as two benzofuran rings are formed in a single synthetic sequence. This methodology is also successfully extended to the synthesis of benzofuranyl methyl chromane derivatives.